Metamorphic modeling and petrochronology of metapelitic rocks from the Luminárias Nappe, southern Brasília belt (SE Brazil) - Fumes, Regiane Andrade; Luvizotto, George Luiz; Moraes, Renato; Heilbron, Monica; Vlach, Silvio Roberto Farias (Sociedade Brasileira de Geologia, 2019)
Abstract The Luminárias Nappe was formed in the agglutination of West Gondwana. A high-pressure metamorphic gradient oblique to the geological contacts is recorded in metapelitic rocks from this Nappe. In the northern portion, the metamorphic peak conditions are at high-pressure lower-amphibolite facies at 580 ± 4°C and ca. 0.9 GPa (Chl + Ky + St + Ms + Qtz + Rt); in the central portion, they are at high-pressure amphibolite facies at 600 ± 15°C and 1.1 ± 0.3 GPa (St + Bt + Grt + Ms + Qtz + Rt); and in the southern portion, they reach the eclogite facies at 630 ± 13°C and 1.4 ± 0.6 GPa (St + Ky + Grt + Ms + Qtz + Rt). Clockwise metamorphic P-T-t paths are registered in the studied rocks, with temperature and pressure increase followed by a strong decompression with retrograde phases as chloritoid (northern portion), chlorite and ilmenite (central portion) and biotite, chlorite and ilmenite (southern portion). U-Th-PbT monazite ages range from 632 ± 4 Ma (southern portion) to 600 ± 8 Ma (northern portion included crystals in garnet and staurolite). The metamorphic age, the high-pressure conditions calculated in this paper and the clockwise metamorphic path indicate that the tectonic evolution of the Luminárias Nappe rocks is tightly associated with the subduction and collision processes of the southern Brasília belt. The overprint of the younger Ribeira belt is interpreted to be responsible for rock pile tilting, thus producing the oblique metamorphic gradient.
Keywords: West Gondwana; monazite dating; THERMOCALC; single element geothermometer; pseudosection